Natural Disasters - Makna Sabar dalam Konteks Ketahanan Korban Banjir - Arif Chasanul Muna; Ahmad Baihaqi; Muhammad Muhlisin (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
The principal problem in this research includes two things; how does the understanding and implementation of the flood victims Pasirsari villages toward the concept of patience?; What is the process of understanding to the formation and implementation of such forbearance in the context of socio-cultural and religious in Pasirsari? This research is a field research using qualitative methods. Qualitative methods are used to describe the understanding of the flood and how the formation process. The analysis used is descriptive-evaluative analysis, followed by explanatory analysis, critical analysis and comparative analysis. Among the results of this study are among the flood victims identified three aspects of patience, namely ahwal, aqwal, and af'al. So, the internal act aspect of people only covers ahwal residents only. While the act covering external aspects of speech (aqwal) and action (af'al).